Electrolytic copper foil capable of low temperature annealing and preparation method and application thereof
Through the two-stage low-temperature annealing treatment and surface treatment combined with additive regulation, the problem of signal distortion and low-temperature annealing efficiency in the application of electrolytic copper foil in high-frequency and high-speed fields is solved, and the high performance and low-consumption process of electrolytic copper foil is realized.
Patent Information
- Application Number
- CN202311500276.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-11-13
AI Technical Summary
In the prior art, the application of electrolytic copper foil in the field of high-frequency and high-speed is limited by the distortion of the skin effect caused by the increase in signal transmission frequency. At the same time, low-temperature annealing technology is difficult to improve the tensile strength, elongation and bending resistance of electrolytic copper foil under the premise of short time and low energy consumption.
The preparation method of two-stage low-temperature annealing treatment combined with surface treatment and additive regulation includes liquid production, electrolysis, surface treatment and annealing treatment. By regulating the types and ratio of additives, the surface roughness and internal structure of electrolytic copper foil are optimized, internal defects and impurities are reduced, thereby improving the performance of electrolytic copper foil.
It realizes the high tensile strength, elongation and bending resistance of electrolytic copper foil, and is suitable for FCCL processing in high-frequency and high-speed fields, and the preparation process consumes short time and energy consumption.
Smart Images

Figure BDA0004544012320000121 
Figure BDA0004544012320000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic copper foil, and in particular relates to an electrolytic copper foil capable of low temperature annealing, a preparation method and application thereof. Background Art
[0002] Flexible copper clad laminate (FCCL) is a processing substrate material for flexible printed circuit board (FPC), which is composed of flexible insulating base film and metal foil. Compared with rigid copper clad laminate, FCCL has the advantages of being thin, light and bendable. The produced FPC has the characteristics of high wiring density, lightness, bendability, and three-dimensional assembly. FCCL has been widely used in electronic products such as aerospace equipment, military guidance systems, mobile phones, digital cameras, automotive satellite positioning devices, LCD TVs, laptops, wearable devices, etc. Most of the metal foil used for FCCL is copper foil, including electrolytic copper foil and rolled copper foil. In recent years, with the improvement of electrolytic copper foil production technology, the bending resistance of electrolytic copper foil has been very close to that of rolled copper foil of the same specification. It can achieve a higher elongation while controlling the surface roughness within a specific range. In addition, electrolytic copper foil has obvious advantages in price. More and more FCCL manufacturers have begun to use electrolytic copper foil instead of rolled copper foil.
[0003] The high speed / high frequency of signals means that signal transmission is increasingly concentrated on the "surface" of the conductor (called skin effect). For example, when the frequency reaches 1GHz, the signal transmission thickness on the conductor surface is only 2.1μm; when the signal transmission frequency is increased to 10GHz, the signal transmission thickness on the conductor surface is 0.70μm. If high-speed FPC continues to use electrolytic copper foil with conventional roughness, the result is that as the signal transmission frequency increases, the signal "distortion" caused by the skin effect will become more and more serious. Therefore, the application of low-roughness electrolytic copper foil on current high-speed materials is becoming more and more widespread, and VLP-grade electrolytic copper foil has become standard.
[0004] In the prior art, in order to make the electrolytic copper foil more suitable for FCCL in the high-frequency and high-speed field, the electrolytic copper foil needs to control the surface roughness of the electrolytic copper foil to be at the VLP level (processing surface roughness Rz≤2.0μm), and multiple methods are also used to regulate the mechanical properties of the electrolytic copper foil. For example, patent application CN115478305A discloses a preparation method and additives of electrolytic copper foil for lithium-ion batteries with high bending resistance, and improves the bending resistance of the electrolytic copper foil by screening the raw material components of the additives including bisbenzenesulfonimide, fish glue, polypropylene glycol, dextrin and sodium dimethylformamidopropane sulfonate. However, this technical solution will cause defects and impurities inside the electrolytic copper foil, resulting in excessive warpage of the electrolytic copper foil, and even fish scale patterns. Patent application CN106536791A discloses an electrolytic copper foil and a method for manufacturing the same, a collector for a lithium secondary battery comprising the electrolytic copper foil, and a lithium secondary battery. The electrolytic copper foil is annealed (annealed at 190°C for 1 hour) to improve the elongation and bending resistance of the electrolytic copper foil. However, the annealing temperature of the process is high, and the process is too time-consuming and energy-intensive.
[0005] Therefore, there is a need for a preparation process for electrolytic copper foil that can be annealed at low temperature, has short time consumption, low energy consumption, and has high tensile strength, elongation, and bending resistance. Summary of the invention
[0006] The present invention aims at solving the problems in the prior art and provides an electrolytic copper foil capable of low temperature annealing and a preparation method and application thereof. The preparation process of the electrolytic copper foil is time-saving and energy-saving, and the prepared electrolytic copper foil has high tensile strength, elongation and bending resistance.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] In one aspect, the present invention provides a method for preparing an electrolytic copper foil capable of low temperature annealing, comprising the following steps:
[0009] S1, liquid preparation: reacting the copper raw material with dilute sulfuric acid to generate a copper sulfate solution;
[0010] S2, electrolysis: after filtering the copper sulfate solution, adding chloride ions and additives to obtain an electrolyte, electrolyzing the electrolyte to obtain raw foil; the additives include a leveling agent, a brightener and a moving agent;
[0011] S3, surface treatment: performing surface treatment on the raw foil to obtain surface treated raw foil; the surface treatment comprises at least one of pickling, roughening, curing, washing, anti-oxidation, passivation and spraying silane;
[0012] S4, annealing treatment: subjecting the raw foil after surface treatment to two-stage annealing treatment to obtain the electrolytic copper foil capable of low temperature annealing.
[0013] Preferably, the copper raw material in step S1 includes at least one of copper wire, copper rod, copper block and copper powder.
[0014] Preferably, the conditions for electrolytic foil production in step S2 are: current density of 60-62A / m 2 , the flow rate of electrolyte is 30-35m 3 / h, the electrolyte temperature is 48-50℃.
[0015] Preferably, the total amount of the additive in step S2 is 18-30 mg / L.
[0016] Preferably, the mass ratio of the leveling agent, brightener and moving agent in step S2 is 0.5-1:1:1-2.
[0017] Further preferably, the mass ratio of the leveling agent, brightener and moving agent in step S2 is 0.8-1:1:1-2.
[0018] Most preferably, the mass ratio of the leveling agent, the brightening agent and the moving agent in step S2 is 1:1:1.
[0019] Preferably, the leveling agent in step S2 is tetrahydrothiazolidinethione and / or polyethyleneimine; the brightening agent is at least one of hexylbenzyl ammonium salt, sodium polydisulfide propane sulfonate and sodium mercaptoimidazole propane sulfonate; and the moving agent is hydroxyethyl cellulose and / or polyethylene glycol.
[0020] Preferably, the viscosity of the hydroxyethyl cellulose in a 2 wt. % aqueous solution at 20° C. is 500 mPa.s.
[0021] Preferably, the molecular weight of the polyethylene glycol is 4000-6000 Da; the molecular weight of the polyethylene imine is 4000-10000 Da.
[0022] Preferably, the concentration of the tetrahydrothiazolidinethione is 4.0-6.0 mg / L, the concentration of the polyethyleneimine is 2.0-4.0 mg / L, the concentration of the hexylbenzyl ammonium salt is 1.5-2.5 mg / L, the concentration of the sodium polydisulfide propane sulfonate is 3.0-5.0 mg / L, the concentration of the sodium mercaptoimidazole propane sulfonate is 1.5-2.5 mg / L, the concentration of the hydroxyethyl cellulose is 3.0-5.0 mg / L, and the concentration of the polyethylene glycol is 2.0-4.0 mg / L.
[0023] Preferably, the pickling conditions in step S3 are: acid concentration 140-150 g / L, temperature 30-40°C; the curing conditions in step S3 are: three-time curing using a curing liquid, the curing liquid contains copper ions with a concentration of 50-56 g / L and sulfuric acid with a concentration of 90-120 g / L, and the temperature of the curing liquid is 40-46°C.
[0024] Preferably, the roughening conditions in step S3 are as follows: roughening is performed three times using a roughening solution, wherein the roughening solution contains copper ions at a concentration of 12-14 g / L, sulfuric acid at a concentration of 120-130 g / L, and sodium tungstate at a concentration of 60-80 mg / L during the first roughening, and the temperature of the roughening solution is 30-35°C; the roughening solution contains copper ions at a concentration of 12-16 g / L and sulfuric acid at a concentration of 120-150 g / L during the second roughening, and the temperature of the roughening solution is 30-34°C; the roughening solution contains copper ions at a concentration of 12-16 g / L and sulfuric acid at a concentration of 120-150 g / L during the third roughening, and the temperature of the roughening solution is 30-34°C.
[0025] Preferably, the conditions for the water washing in step S3 are: temperature 25-35° C., pH 6.8-7.2, and ultrapure water.
[0026] Preferably, the anti-oxidation condition in step S3 is: using an anti-oxidation liquid for anti-oxidation treatment, wherein the anti-oxidation liquid contains nickel ions at a concentration of 1.5-2.5 g / L, zinc ions at a concentration of 3.5-4.5 g / L, and K ions at a concentration of 70-100 g / L. 4 P 2 O 7 , the pH of the anti-oxidation liquid is 10-11 and the temperature is 25-35℃.
[0027] Preferably, the passivation conditions in step S3 are: passivation treatment is performed using a passivation solution containing 2.0-2.5 g / L of chromium ions and 70-100 g / L of K 4 P 2 O 7 , the pH of the passivation solution is 11-12 and the temperature is 25-35℃.
[0028] Preferably, the water washing needs to be performed three times: the first water washing is required after the three solidification treatments, the second water washing is performed after the anti-oxidation treatment, and the third water washing is performed after the passivation treatment.
[0029] Preferably, the conditions for spraying silane in step S3 are: spraying an organic silane coupling agent, the concentration of the organic silane coupling agent is 1.0-1.5 g / L, the pH is 9-12, and the temperature is 25-35°C.
[0030] Preferably, the organic silane coupling agent includes but is not limited to at least one of an ethoxy silane coupling agent, an amino silane coupling agent, a methacrylate silane coupling agent, an epoxy silane coupling agent, and a mercapto silane coupling agent.
[0031] Preferably, the conditions of the two-stage annealing treatment in step S4 are: the first stage annealing treatment is to bake the electrolytic copper foil in an oven during the winding process at a temperature of 130-140°C for 5-10 seconds; the second stage annealing treatment is to bake the electrolytic copper foil in an oven together with the winding shaft after the foil is wound at a temperature of 60-80°C for 6-8 hours.
[0032] On the other hand, the present invention provides an electrolytic copper foil capable of low temperature annealing, which is prepared by the above-mentioned preparation method.
[0033] Preferably, the electrolytic copper foil contains copper ions at a concentration of 80-90 g / L, sulfuric acid at a concentration of 110-120 g / L, and chloride ions at a concentration of 1.0-1.5 mg / L.
[0034] The present invention also provides an application of the electrolytic copper foil or the electrolytic copper foil prepared by the above preparation method in a flexible copper clad laminate.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The preparation process of the electrolytic copper foil in the present invention is annealed at low temperature, which takes a short time and consumes little energy;
[0037] (2) The present invention can provide an electrolytic copper foil with fine and uniform crystallization, gentle contour, stable peak value, uniform copper nodule size, and few internal defects and impurities by regulating the types and proportions of raw foil additives; by regulating the concentration of coarse curing additives and copper acid, a VLP grade roughness treatment surface is obtained on the surface of the electrolytic copper foil; and by two-step low-temperature treatment, the stress inside the electrolytic copper foil is further released, so that the electrolytic copper foil after annealing has high tensile strength, elongation, bending resistance and other properties, and can be used for the processing of FCCL in the high-frequency and high-speed fields. DETAILED DESCRIPTION
[0038] The present invention is described below through specific embodiments to make the technical solution of the present invention easier to understand and grasp, but the present invention is not limited thereto, and the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0039] The endpoints and any value of the scope disclosed in this article are not limited to the accurate scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Unless the context clearly indicates otherwise, the singular form "one", "a kind of" and "described" as used herein include singular and plural indicators. The numerical range described by the endpoint is included in all numerical values and fractions within the corresponding range, as well as the described endpoint.
[0040] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0041] Example 1 A method for preparing an electrolytic copper foil capable of low temperature annealing
[0042] Step 1, liquid preparation: add copper wire into a copper dissolving tank, add pure water, oxygen and dilute sulfuric acid, stir, heat and react to generate copper sulfate solution;
[0043] Step 2, electrolysis: The copper sulfate solution generated in step 1 is filtered through a filter, transported to a high-level tank, and then chloride ions and additives are added to obtain an electrolyte, which is then transported to an electrolytic cell for electrolysis to produce raw foil. The electrolysis conditions are a current density of 62A / m 2 , the flow rate of electrolyte is 30m 3 / h.
[0044] The copper ion content in the electrolyte is 85 g / L, the sulfuric acid content is 115 g / L, the chloride ion content is 1.0 mg / L, the total amount of additives is 18 mg / L, and the electrolyte temperature is 48°C.
[0045] The additive is an aqueous solution containing hexylbenzyl ammonium salt (PPNI), sodium polydisulfide propane sulfonate (SPS), sodium mercaptoimidazole propane sulfonate (MESS), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), tetrahydrothiazolidinethione and polyethyleneimine. Among them, the PPNI, SPS and MESS are used as brighteners, the HEC and PEG are used as moving agents, and the tetrahydrothiazolidinethione and polyethyleneimine are used as leveling agents. The mass ratio of the leveling agent, the brightener and the moving agent is 1:1:1.
[0046] The viscosity of the HEC in a 2 wt. % aqueous solution at 20° C. is 500 mPa.s, the molecular weight of PEG is 5000 Da, and the molecular weight of polyethyleneimine is 6000 Da.
[0047] The concentration of PPNI was 1.5 mg / L, the concentration of SPS was 3.0 mg / L, the concentration of MESS was 1.5 mg / L; the concentration of HEC was 3.0 mg / L, the concentration of PEG was 3.0 mg / L; the concentration of tetrahydrothiazolidinethione was 4.0 mg / L, and the concentration of polyethyleneimine was 2.0 mg / L.
[0048] Step 3: Surface treatment of the raw foil obtained by the electrolysis process in step 2:
[0049] (1) Pickling: The concentration of sulfuric acid in the pickling tank is 145 g / L and the temperature is 35 °C;
[0050] (2) Roughening 1: the roughening tank contains a roughening solution, the copper ion concentration in the roughening solution is 13 g / L, the sulfuric acid concentration is 125 g / L, the sodium tungstate concentration is 60 mg / L, and the roughening solution temperature is 32°C; Roughening 2: the copper ion concentration in the roughening tank is 13 g / L, the sulfuric acid concentration is 130 g / L, and the temperature is 32°C; Roughening 3: the copper ion concentration in the roughening tank is 14 g / L, the sulfuric acid concentration is 130 g / L, and the temperature is 32°C;
[0051] (3) Curing 1: the copper ion concentration in the curing tank is 52 g / L, the sulfuric acid concentration is 100 g / L, and the temperature is 42°C; Curing 2: the copper ion concentration in the curing tank is 52 g / L, the sulfuric acid concentration is 100 g / L, and the temperature is 42°C; Curing 3: the copper ion concentration in the curing tank is 52 g / L, the sulfuric acid concentration is 100 g / L, and the temperature is 42°C;
[0052] (4) Washing: using ultrapure water, temperature 30°C, pH 7.0;
[0053] (5) Anti-oxidation: The concentration of nickel in the anti-oxidation treatment tank is 2.0 g / L, the concentration of zinc is 4.0 g / L, and the concentration of K 4 P 2 O 7 The concentration is 80 g / L, the pH value is 10, and the temperature is 30°C;
[0054] (6) Washing: using ultrapure water, temperature 30°C, pH 7.0;
[0055] (7) Passivation: The chromium concentration in the passivation treatment tank is 2.2 g / L, K 4 P 2 O 7 The concentration is 80g / L, the pH is 11, and the temperature is 30℃.
[0056] (8) Washing: using ultrapure water, temperature 30 °C, pH 7.0;
[0057] (9) Silane spraying: the concentration of γ-glycidyloxypropyltrimethoxysilane coupling agent is 1.2 g / L, the pH is 10, and the temperature is 30°C.
[0058] Step 4, annealing treatment: including 1-stage annealing and 2-stage annealing treatment. The 1-stage annealing is to bake the electrolytic copper foil in an oven during the winding process, the baking temperature is 130°C, and the time is 10s; the 2-stage annealing is to bake the electrolytic copper foil in an oven together with the winding shaft after the foil is rolled, the baking temperature is 60°C, the time is 8h, and then cooled to room temperature under natural conditions, so as to obtain the electrolytic copper foil that can be annealed at low temperature.
[0059] Example 2 A method for preparing an electrolytic copper foil capable of low temperature annealing
[0060] Step 1, liquid preparation: add copper wire into a copper dissolving tank, add pure water, oxygen and dilute sulfuric acid, stir, heat and react to generate copper sulfate solution;
[0061] Step 2, electrolysis: The copper sulfate solution generated in step 1 is filtered through a filter, transported to a high-level tank, and then chloride ions and additives are added to obtain an electrolyte, which is then transported to an electrolytic cell for electrolysis to produce raw foil. The electrolysis conditions are a current density of 60A / m 2 , the flow rate of electrolyte is 32m 3 / h.
[0062] The copper ion content in the electrolyte is 80 g / L, the sulfuric acid content is 110 g / L, the chloride ion content is 1.0 mg / L, the total amount of additives is 30 mg / L, and the electrolyte temperature is 50°C.
[0063] The additive is an aqueous solution containing hexylbenzyl ammonium salt (PPNI), sodium polydisulfide propane sulfonate (SPS), sodium mercaptoimidazole propane sulfonate (MESS), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), tetrahydrothiazolidinethione and polyethyleneimine. Among them, the PPNI, SPS and MESS are used as brighteners, the HEC and PEG are used as moving agents, and the tetrahydrothiazolidinethione and polyethyleneimine are used as leveling agents. The mass ratio of the leveling agent, the brightener and the moving agent is 0.8:1:2.
[0064] The viscosity of the HEC in a 2 wt. % aqueous solution at 20° C. is 500 mPa.s, the molecular weight of PEG is 6000 Da, and the molecular weight of polyethyleneimine is 10000 Da.
[0065] The concentration of PPNI was 2.5 mg / L, the concentration of SPS was 5.0 mg / L, the concentration of MESS was 2.5 mg / L; the concentration of HEC was 5.0 mg / L, the concentration of PEG was 5.0 mg / L; the concentration of tetrahydrothiazolidinethione was 6.0 mg / L, and the concentration of polyethyleneimine was 4.0 mg / L.
[0066] Step 3: Surface treatment of the raw foil obtained by the electrolysis process in step 2:
[0067] (1) Pickling: The concentration of sulfuric acid in the pickling tank is 140 g / L and the temperature is 40 °C;
[0068] (2) Roughening 1: the roughening tank contains a roughening solution, the copper ion concentration in the roughening solution is 14 g / L, the sulfuric acid concentration is 130 g / L, the sodium tungstate concentration is 80 mg / L, and the roughening solution temperature is 35°C; Roughening 2: the copper ion concentration in the roughening tank is 16 g / L, the sulfuric acid concentration is 150 g / L, and the temperature is 30°C; Roughening 3: the copper ion concentration in the roughening tank is 16 g / L, the sulfuric acid concentration is 120 g / L, and the temperature is 30°C;
[0069] (3) Curing 1: the copper ion concentration in the curing tank is 56 g / L, the sulfuric acid concentration is 90 g / L, and the temperature is 46°C; Curing 2: the copper ion concentration in the curing tank is 56 g / L, the sulfuric acid concentration is 90 g / L, and the temperature is 46°C; Curing 3: the copper ion concentration in the curing tank is 56 g / L, the sulfuric acid concentration is 90 g / L, and the temperature is 46°C;
[0070] (4) Washing: using ultrapure water, temperature 25 °C, pH 6.8;
[0071] (5) Anti-oxidation: The concentration of nickel in the anti-oxidation treatment tank is 1.5 g / L, the concentration of zinc is 4.5 g / L, and the concentration of K 4 P 2 O 7 The concentration is 100 g / L, the pH is 11, and the temperature is 25°C;
[0072] (6) Washing: using ultrapure water, temperature 25 °C, pH 6.8;
[0073] (7) Passivation: The chromium concentration in the passivation treatment tank is 2.5 g / L, K 4 P 2 O 7 The concentration is 70g / L, the pH is 12, and the temperature is 35℃.
[0074] (8) Washing: using ultrapure water, temperature 25 °C, pH 6.8;
[0075] (9) Silane spraying: the concentration of acetyltrimethoxysilane is 1.0 g / L, the pH is 12, and the temperature is 35°C.
[0076] Step 4, annealing treatment: including 1-stage annealing and 2-stage annealing treatment. The 1-stage annealing is to bake the electrolytic copper foil in an oven during the winding process, the baking temperature is 140°C, and the time is 5s; the 2-stage annealing is to bake the electrolytic copper foil in an oven together with the winding shaft after the foil is rolled, the baking temperature is 80°C, the time is 6h, and then cooled to room temperature under natural conditions, so as to obtain the electrolytic copper foil that can be annealed at low temperature.
[0077] Example 3 A method for preparing an electrolytic copper foil capable of low temperature annealing
[0078] Step 1, liquid preparation: add copper wire into a copper dissolving tank, add pure water, oxygen and dilute sulfuric acid, stir, heat and react to generate copper sulfate solution;
[0079] Step 2, electrolysis: The copper sulfate solution generated in step 1 is filtered through a filter, transported to a high-level tank, and then chloride ions and additives are added to obtain an electrolyte, which is then transported to an electrolytic cell for electrolysis to produce raw foil. The electrolysis conditions are a current density of 60A / m 2 , the flow rate of electrolyte is 35m 3 / h.
[0080] The copper ion content in the electrolyte is 90 g / L, the sulfuric acid content is 120 g / L, the chloride ion content is 1.5 mg / L, the total amount of additives is 18 mg / L, and the electrolyte temperature is 48°C.
[0081] The additive is an aqueous solution containing hexylbenzyl ammonium salt (PPNI), sodium polydisulfide propane sulfonate (SPS), sodium mercaptoimidazole propane sulfonate (MESS), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), tetrahydrothiazolidinethione and polyethyleneimine. Among them, the PPNI, SPS and MESS are used as brighteners, the HEC and PEG are used as moving agents, and the tetrahydrothiazolidinethione and polyethyleneimine are used as leveling agents. The mass ratio of the leveling agent, the brightener and the moving agent is 0.5:1:2.
[0082] The viscosity of the HEC in a 2 wt. % aqueous solution at 20° C. is 500 mPa.s, the molecular weight of PEG is 4000 Da, and the molecular weight of polyethyleneimine is 4000 Da.
[0083] The concentration of PPNI was 1.5 mg / L, the concentration of SPS was 3.0 mg / L, the concentration of MESS was 1.5 mg / L; the concentration of HEC was 3.0 mg / L, the concentration of PEG was 3.0 mg / L; the concentration of tetrahydrothiazolidinethione was 4.0 mg / L, and the concentration of polyethyleneimine was 2.0 mg / L.
[0084] Step 3: Surface treatment of the raw foil obtained by the electrolysis process in step 2:
[0085] (1) Pickling: The concentration of sulfuric acid in the pickling tank is 150g / L and the temperature is 30°C;
[0086] (2) Roughening 1: the roughening tank contains a roughening solution, the copper ion concentration in the roughening solution is 12 g / L, the sulfuric acid concentration is 120 g / L, the sodium tungstate concentration is 70 mg / L, and the roughening solution temperature is 30°C; Roughening 2: the copper ion concentration in the roughening tank is 12 g / L, the sulfuric acid concentration is 120 g / L, and the temperature is 34°C; Roughening 3: the copper ion concentration in the roughening tank is 12 g / L, the sulfuric acid concentration is 150 g / L, and the temperature is 34°C;
[0087] (3) Curing 1: the copper ion concentration in the curing tank is 50 g / L, the sulfuric acid concentration is 120 g / L, and the temperature is 40°C; Curing 2: the copper ion concentration in the curing tank is 50 g / L, the sulfuric acid concentration is 120 g / L, and the temperature is 40°C; Curing 3: the copper ion concentration in the curing tank is 50 g / L, the sulfuric acid concentration is 120 g / L, and the temperature is 40°C;
[0088] (4) Washing: using ultrapure water, temperature 35°C, pH 7.2;
[0089] (5) Anti-oxidation: The concentration of nickel in the anti-oxidation treatment tank is 2.5 g / L, the concentration of zinc is 3.5 g / L, and the concentration of K 4 P 2 O 7 The concentration is 70 g / L, the pH is 10, and the temperature is 35°C;
[0090] (6) Washing: using ultrapure water, temperature 35 °C, pH 7.2;
[0091] (7) Passivation: The chromium concentration in the passivation treatment tank is 2.0 g / L, K 4 P 2 O 7 The concentration is 100g / L, the pH is 11, and the temperature is 25℃.
[0092] (8) Washing: using ultrapure water, temperature 35 °C, pH 7.2;
[0093] (9) Silane spraying: γ-aminopropyltriethoxysilane concentration is 1.5 g / L, pH is 9, and temperature is 25°C.
[0094] Step 4, annealing treatment: including 1-stage annealing and 2-stage annealing treatment. The 1-stage annealing is to bake the electrolytic copper foil in an oven during the winding process, the baking temperature is 135°C, and the time is 10s; the 2-stage annealing is to bake the electrolytic copper foil in an oven together with the winding shaft after the foil is rolled, the baking temperature is 70°C, the time is 7h, and then cooled to room temperature under natural conditions, so as to obtain the electrolytic copper foil that can be annealed at low temperature.
[0095] Comparative Example 1
[0096] Compared with Example 1, the only difference is:
[0097] In step 2, the total amount of additives in the electrolyte is 24 mg / L, wherein the leveling agent, brightener and moving agent are present in the electrolyte at a mass ratio of 2:3:2. The concentration of the brightener PPNI is 1.5 mg / L, the concentration of SPS is 3.0 mg / L, and the concentration of MESS is 1.5 mg / L; the concentration of the moving agent HEC is 4.0 mg / L, and the concentration of PEG is 4.0 mg / L; the concentration of the leveling agent tetrahydrothiazolidinethione is 4.0 mg / L, and the concentration of polyethyleneimine is 2.0 mg / L.
[0098] The other steps are the same as those in the first embodiment.
[0099] Comparative Example 2
[0100] Compared with Example 1, the only difference is:
[0101] In step 2, the concentration of PPNI in the electrolyte is 1.0 mg / L, the concentration of SPS is 4.0 mg / L, and the concentration of MESS is 1.0 mg / L; the concentration of HEC is 3.0 mg / L, and the concentration of PEG is 3.0 mg / L; the concentration of tetrahydrothiazolidinethione is 3.0 mg / L, and the concentration of polyethyleneimine is 3.0 mg / L.
[0102] The other steps are the same as those in the first embodiment.
[0103] Comparative Example 3
[0104] Compared with Example 1, the only difference is:
[0105] In step 3, the sodium tungstate concentration during the roughening process 1 is 100 mg / L.
[0106] In step 4, the first stage annealing is to bake the electrolytic copper foil in an oven during the winding process, the baking temperature is 150°C, and the time is 5s; the second stage annealing is to bake the electrolytic copper foil in an oven together with the winding shaft after the foil is wound, the baking temperature is 100°C, the time is 6h, and then cooled to room temperature under natural conditions, so as to obtain the electrolytic copper foil that can be annealed at a low temperature.
[0107] The other steps are the same as those in the first embodiment.
[0108] Effect example
[0109] According to "GB-T 5230-2020 Electrolytic Copper Foil for Printed Boards", the electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-3 that can be annealed at low temperatures were tested to obtain the physical properties shown in the following table. It can be seen that the electrolytic copper foils that can be annealed at low temperatures in Examples 1-3 of the present invention have a room temperature tensile strength of ≥400MPa, a room temperature elongation of ≥10.0%, a high temperature tensile strength of ≥260MPa, a high temperature elongation of ≥21.0%, a treated surface roughness of Rz ≤2.00μm, a peel strength of ≥0.80N / mm, and a folding resistance of ≥3000 times. It meets the testing standards and can provide FCCL manufacturers with electrolytic copper foil raw materials with high elongation, high bending resistance, and low warping.
[0110] Table 1 Physical properties of electrolytic copper foil
[0111]
[0112]
[0113] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an electrolytic copper foil capable of low temperature annealing, characterized in that: The following steps are involved: S1, liquid preparation: reacting the copper raw material with dilute sulfuric acid to generate a copper sulfate solution; S2, electrolysis: after filtering the copper sulfate solution, adding chloride ions and additives to obtain an electrolyte, electrolyzing the electrolyte to obtain raw foil; the additives include a leveling agent, a brightener and a moving agent; S3, surface treatment: performing surface treatment on the raw foil to obtain surface treated raw foil; the surface treatment comprises at least one of pickling, roughening, curing, washing, anti-oxidation, passivation and spraying silane; S4, annealing treatment: subjecting the surface treated raw foil to two-stage annealing treatment to obtain the electrolytic copper foil capable of low temperature annealing; The total amount of the additive in step S2 is 18-30 mg / L; In step S2, the mass ratio of the leveling agent, the brightening agent and the moving agent is 0.5-1:1:1-2, the leveling agent is 4.0-6.0 mg / L tetrahydrothiazolidinethione and 2.0-4.0 mg / L polyethyleneimine, the brightening agent is 1.5-2.5 mg / L hexylbenzyl ammonium salt, 3.0-5.0 mg / L sodium polydisulfide propane sulfonate and 1.5-2.5 mg / L sodium mercaptoimidazole propane sulfonate, and the moving agent is 3.0-5.0 mg / L hydroxyethyl cellulose and 2.0-4.0 mg / L polyethylene glycol; In step S3, the roughening liquid for the first roughening comprises 60-80 mg / L of sodium tungstate; The conditions of the two-stage annealing treatment in step S4 are: the temperature of the first stage annealing treatment is 130-140° C., and the time is 5-10 seconds; the temperature of the second stage annealing treatment is 60-80° C., and the time is 6-8 hours.
2. The preparation method according to claim 1, characterized in that: The copper raw material described in step S1 includes at least one of copper wire, copper rod, copper block and copper powder.
3. The preparation method according to claim 1, characterized in that: The electrolyte in step S2 contains copper ions at a concentration of 80-90 g / L, sulfuric acid at a concentration of 110-120 g / L, and chloride ions at a concentration of 1.0-1.5 mg / L. The conditions for electrolytic foil production in step S2 are: a current density of 60-62 A / m 2 , the flow rate of electrolyte is 30-35m 3 / h, the electrolyte temperature is 48-50℃.
4. The preparation method according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 4000-6000Da; the molecular weight of the polyethyleneimine is 4000-10000Da.
5. The preparation method according to claim 1, characterized in that: The conditions for pickling in step S3 are: acid concentration 140-150 g / L, temperature 30-40° C.; The roughening conditions of step S3 are as follows: the roughening solution is used for three roughening processes, the roughening solution also includes copper ions with a concentration of 12-14 g / L and sulfuric acid with a concentration of 120-130 g / L during the first roughening process, and the temperature of the roughening solution is 30-35°C; the roughening solution contains copper ions with a concentration of 12-16 g / L and sulfuric acid with a concentration of 120-150 g / L during the second roughening process, and the temperature of the roughening solution is 30-34°C; the roughening solution contains copper ions with a concentration of 12-16 g / L and sulfuric acid with a concentration of 120-150 g / L during the third roughening process, and the temperature of the roughening solution is 30-34°C; The curing conditions in step S3 are: three times of curing using a curing liquid, the curing liquid contains copper ions with a concentration of 50-56 g / L and sulfuric acid with a concentration of 90-120 g / L, and the temperature of the curing liquid is 40-46°C.
6. The preparation method according to claim 1, characterized in that: The water washing conditions in step S3 are: temperature 25-35°C, pH 6.8-7.2; the anti-oxidation conditions in step S3 are: anti-oxidation treatment using an anti-oxidation liquid, the anti-oxidation liquid contains nickel ions at a concentration of 1.5-2.5 g / L, zinc ions at a concentration of 3.5-4.5 g / L and K4P2O7 at a concentration of 70-100 g / L, the pH of the anti-oxidation liquid is 10-11, and the temperature is 25-35°C.
7. The preparation method according to claim 1, characterized in that: The passivation conditions in step S3 are: passivation treatment is performed using a passivation solution, the passivation solution contains chromium ions at a concentration of 2.0-2.5 g / L and K4P2O7 at a concentration of 70-100 g / L, the pH of the passivation solution is 11-12, and the temperature is 25-35°C; the conditions for spraying silane in step S3 are: spraying an organic silane coupling agent, the concentration of the organic silane coupling agent is 1.0-1.5 g / L, the pH is 9-12, and the temperature is 25-35°C.
8. An electrolytic copper foil capable of low temperature annealing, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the electrolytic copper foil according to claim 8 or the electrolytic copper foil prepared by the preparation method according to any one of claims 1 to 7 in a flexible copper clad laminate.
Citation Information
Patent Citations
Electrolytic copper foil and manufacturing method therefor, current collector for lithium secondary battery comprising electrolytic copper foil, and lithium secondary battery
CN106536791A
Preparation method of electrolytic copper foil with high bending resistance for lithium ion battery and additive of electrolytic copper foil
CN115478305A
Method for recovering copper from brownification waste liquid
CN103510107A
Method for manufacturing high-roughness electronic copper foil for ceramic-based high-frequency electronic copper-clad plate
CN105050331A
Preparation method of high-tensile-resistance electrolytic copper foil for lithium battery
CN110760898A